IMF Staff papers : Volume 34 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1987)
In the middle of 1985 Argentina and Israel launched frontal attacks on inflation which succeeded in reducing it drastically during the first year without very significant costs in employment and output. Despite basic differences in the countries' structures, the programs were similar in their design and their effects. This paper covers some of these similarities in the implementation and the results of the two stabilization programs, and analyzes the rationale of the underlying conception of the plans. The focus is on the strategy for the transitional period, and the ability of the programs to sustain price stability.